Stanley Cavell - Eldridge, Richard Thomas, 1953- (Contemporary philosophy in focus., 2003)
This is the first attempt to describe and assess the full range of Cavell's work. There are new accounts of Cavell's contribution to the philosophy of mind & language, the theory of action, ethics, aesthetics, Romanticism, American philosophy, Shakespeare, film & opera.